HOW TO MEASURE ADEQUACY OF TECHNICAL PROVISIONS IN GENERAL INSURANCE – PRACTICAL PERSPECTIVE - Zsoldos, Peter (European Scientific Journal, ESJ, 2014)
The goal of this article is to outline possible applications of liability adequacy test (LAT) for non-life business applied by the insurance companies according to local accounting policy and IFRS. As LAT is very indicative tool to quantify adequacy of liabilities, therefore every non-life insurance company should apply certain method of LAT. In the first part, the article focused on the legislative framework and general descriptions of LAT according to IFRS 4. The general definitions and possible applied methodology are described in the next section. The final part is dedicated to calculations and illustrative examples of the topic.